2016
DOI: 10.1111/fme.12135
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assessment of the physiological impacts caused by catch‐and‐release angling on blue‐finned mahseer (Tor sp.) of the Cauvery River, India

Abstract: Forty‐nine blue‐finned mahseer (Tor sp.; mean total length 458 ± 20 mm) were angled using a range of bait/lure types, angling and air exposure times in water that averaged 27 ± 2 °C over the course of the assessment. No cases of mortality were observed, and rates of moderate and major injury were low, with 91% of mahseer hooked in the mouth. More extreme physiological disturbances (i.e. blood lactate, glucose, pH) in mahseer were associated with longer angling times. Sixteen fish (33%) exhibited at least one f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Typically, the timing of blood sampling has been either from the end of timed air exposure treatments (e.g. Bower et al, 2016b;Lennox et al, 2016) or immediately following reflex impairment tests (e.g. Bower et al, 2016b;Pinder et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Typically, the timing of blood sampling has been either from the end of timed air exposure treatments (e.g. Bower et al, 2016b;Lennox et al, 2016) or immediately following reflex impairment tests (e.g. Bower et al, 2016b;Pinder et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Bower et al, 2016b;Lennox et al, 2016) or immediately following reflex impairment tests (e.g. Bower et al, 2016b;Pinder et al, 2016). In considering the limitations of available tools and their utility in C&R studies, Cooke et al (2013) concluded there is no optimal protocol for blood sampling in the field and, instead, recommended that studies should focus on the comparison of treatment groups as opposed to placing inappropriate confidence in absolute values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hühn & Arlinghaus ; Bower et al . ; Olaussen ). Although with a primary objective to reduce mortality, catch‐and‐release can also lead to fitness impacts (Richard et al .…”
Section: Recent Developments In Recreational Fisheries Science and Mamentioning
confidence: 99%
“…Accordingly, the utility of catch-and-release angling and its effects on individual fish and populations has received considerable attention in recent years (e.g. H€ uhn & Arlinghaus 2011;Bower et al 2016;Olaussen 2016). Although with a primary objective to reduce mortality, catch-and-release can also lead to fitness impacts (Richard et al 2013) and affect entire populations (Coggins et al 2007;Johnston et al 2015), in turn demanding continued attention by scientists and managers to develop science-based bestpractice guidelines (Arlinghaus et al 2007).…”
Section: Ecological Impactsmentioning
confidence: 99%